A study on intermediate buffer layer of coated Fiber Bragg Grating cryogenic temperature sensors. Issue 1 (November 2015) - Freitas, R; Araujo, F; Araujo, J; Neumann, H; Ramalingam, R
Abstract: The sensor characteristics of a coated Fiber Bragg grating (FBG) thermal sensor for cryogenic temperatures depends mainly on the coating materials. The sensitivity of the coated FBG can be improved by enhancing the effective thermal strain transfer between the different layers and the bare FBG. The dual coated FBG's has a primary layer and the secondary layer. The primary coating acts as an intermediate buffer between the secondary coating and the bare FBG. The outer secondary coating is normally made of metals with high thermal expansion coefficient. In this work, a detailed study is carried out on chromium and titanium intermediate buffer layers with various coating thicknesses and combinations. To improve the sensitivity, the secondary coating layer was tested with Indium, Lead and Tin. The sensors were then calibrated in a cryogenic temperature calibration facility at Institute of Technical Physics (ITEP), Karlsruhe Institute of Technology. The sensors were subjected to several thermal cycles between 4.2 and 80 K to study the sensor performance and its thermal characteristics. The sensor exhibits a Bragg wavelength shift of 13pm at 20K. The commercially available detection equipment with a resolution of 1pm can result in a temperature resolution of 0.076 K at 20K.